Ideology and the promotion of social change - Becker, Julia C (Current opinion in behavioral sciences, 2020)
•Ideology needs to be incorporated into models of collective action.•Liberals are more likely than conservatives to promote social change.•Differentiation between progressive and reactionary social change is important.•Left-wing individuals promote progressive social change.•Right-wing individuals promote reactionary social change. Most models predicting collective action for social change have not considered the role of ideology. Recent research suggests, however, that ideology is a key variable in predicting social change efforts by illustrating that conservatives are more likely to resist whereas liberals are more likely to promote social change. In this review, I bring two lines of research together showing that not ony liberals but also right-wing populists are interested in collective action for social change. I introduce an integrative framework that endeavors to clarify the relation between ideology and social change by taking the content of socio-political issues into account. I propose that the distinction between progressive and reactionary social change can help to connect different social change intentions with its underlying ideological antecedents.